IT Operations in Retail Banking: A Case Study - Saleheen, Ferdoush; Miraz, Mahadi Hasan; Ramli, Razamin (ResearchGate GmbH, 2014)
E-business has created a remarkable revolution all across the world particularly in the North America, Europe. Even countries in Asia have progressed a lot. To keep with the same pace, Bangladesh is also moving forward. It is a new horizon for Bangladeshi banking industry. Although, most of the nationalized banks even having hundreds of branches covering all over Bangladesh did not progress satisfactorily due to poor IT infrastructure, data synchronization, network coverage and skills within the banks as an end user made this even more challenging. One the other side, private banking sectors are offering in a fast paced environment at par to global context. These research findings are based on primary data gives an opportunity for the industry practitioners to review their operations practice and suggest the intricacies to improve the operational efficiencies in the IT platform to upgrade the E-commerce facilities. The economy has been greatly benefited through using online banking which covered all over Bangladesh. It has made revolution in the rural periphery. Ultimately it has change the life style of the people by bringing them under the umbrella of technology and real time data information